Parental and child factors associated with participation in a randomised control trial of an Internet‐assisted parent training programme. Issue 2 (10th November 2016) - Fossum, Sturla; Ristkari, Terja; Cunningham, Charles; McGrath, Patrick J.; Suominen, Auli; Huttunen, Jukka; Lingley‐Pottie, Patricia; Sourander, Andre
Abstract : Background: Parental training is an effective way to treat and prevent children's conduct problems, but knowledge of who participates in such initiatives is limited. Method: This study examined child and family factors associated with participation in an Internet‐assisted parent training programme. The parents of 4‐year‐old children with high levels of disruptive behaviour in a region of Finland were offered the opportunity to participate in a randomised controlled trial of the Strongest Families Smart Website intervention (SFSW). The participants and nonparticipants were compared using the Strengths and Difficulties Questionnaire (SDQ), duration of child problems and information about family demographics, which were routinely collected prior to randomisation to the SFSW and control group. Results: We found that 464 (64.5%) of the 709 parents of children fulfilling the screening criteria, participated. In the multivariable analysis, nonparticipation was most strongly associated with a child only having minor difficulties [odds ratio (OR): 2.1; 95% confidence interval (CI): 1.5–3.0] and a shorter duration of problems, for less than 12 months (OR: 1.7, 95% CI: 1.2–2.5), after controlling for other child factors. Nonparticipation was significantly associated with mothers spending a shorter time in the education system (OR: 1.6, 95% CI: 1.2–2.3) after controlling for other parental factors. Conclusions: A larger percentage of parents of children with longer lasting and more severe problems seemed to be motivated to participate in this remote parent training programme. Future studies on how to encourage parents with shorter duration of education to participate in early intervention programmes are warranted.